Penatalaksanaan Fisioterapi Pada Kasus Osteoarthritis Genu Sinistra Di RSO Prof. Dr Soeharso Surakarta - Fauzi, Luqman, Agus Widodo, S. Fis., M. Fis (2015)
Background : Osteoarthritis is an abnormality on cartilage ( cartilage ) are characterized by changes in clinical , histological and radiological . This disease is asymmetrical , not inflamed and no components systematically Methods : the methods in the management of this case, using Microwave Diathermy (MWD),Transcutaneus Electrical Nerve Stimulation (TENS), exercise therapy. manually muscle strength (MMT), measuring of the range of motion goneometer, ability of ADL Jette Scale. Objectives :above methods to understand the benefits of MWD, TENS and exercise therapy in reducing pain,increasing range of motions, increasing muscle strength, and increasing of ability ADL. Results :after had given physiotherapy 6 times the results obstained : decreased of pain, increased range of motions, increased muscle strength and then increased ability of functional activity. Conclusion : MWD, TENScan reduce pain in that case. Exercise therapy can increases range of motions, muscle strength, and ability of functional activity. Key words: Osteoarthritis, Microwave Diathermy, Transcutaneus Electrical Nerve Stimulation, exercise therapy.